HUBUNGAN MANUSIA DENGAN LINGKUNGAN DALAM CERPEN KAYU NAGA KARYA KORRIE LAYUN RAMPAN (KAJIAN EKOKRITIK GREG GARRARD) - Liya Yuliyani (MEDAN MAKNA: Jurnal Ilmu Kebahasaan dan Kesastraan, 2023)
This study aims to describe the form of human relations with the natural environment and the forms of natural damage contained in the short story Kayu Naga by Korrie Layun Rampan. The method used in this study is a qualitative descriptive method using Greg Garrard's ecocritical approach. The data source in this study is the short story Kayu Naga by Korrie Layun Rampan. Data collection techniques using reading and note-taking techniques. The results of this study are 1) the relationship between humans and the natural environment in the short story Kayu Naga shows a close relationship between humans and the natural environment and 2) the form of damage to the natural environment contained in the short story Kayu Naga by Korrie Layun Rampan is caused by human activities that destroy forests by felling trees, hunting birds, and clearing land.